Effects of ethanol injection strategies on mixture formation and combustion process in an ethanol direct injection (EDI) plus gasoline port injection (GPI) spark-ignition engine. (15th May 2020) - Zhuang, Yuan; Ma, Yongfei; Qian, Yejian; Teng, Qin; Wang, Chunmei
Abstract: The mixture formation process is vital for ethanol direct injection (EDI) plus gasoline port injection (GPI) engine, as the mixture preparation quality directly affects the combustion process and emission characteristics, especially for the dual-injection system. In this study, engine tests were first conducted to investigate the effects of ethanol injection timings (430 °CA, 570 °CA, 620 °CA and 670 °CA) and injection pressures (40 bar, 60 bar and 90 bar) on engine performance and combustion process. Then, the numerical simulations were performed with the focus on detailed mixture formation process, including in-cylinder flows, wall wetting and fuel evaporation. The experimental and numerical results indicated that the injection timing has a significant effect on the mixture formation in EDI + GPI engine. Due to the long evaporation time and strong in-cylinder TKE, early injection timing (430 °CA) can lead to a uniform mixture and complete combustion. The effect of ethanol injection pressure on mixture formation was not significant at this ethanol injection timing. As the injection timing was retarded, due to the reduced evaporation time, the formation of the homogeneous mixture became harder, and the effect of injection pressure on the mixture preparation became obvious. At injection timing of 620 °CA, high injection pressure generated high fuel spray momentum, which deformed the original in-cylinder vortex, and more ethanol fuel collided on the piston surface and the wall, resulting in uneven distribution of the mixture and poor combustion. When the injection timing was retarded to 670 °CA, the injection pressure of 60 bar could obtain a good balance among the fuel evaporate rate, the amount fuel impinging on the wall and the fuel evaporation time, resulting more complete combustion.